A comprehensive numerical investigation of the impact behaviour of an offshore wind turbine blade due to impact loads during installation. (15th January 2019) - Verma, Amrit Shankar; Vedvik, Nils Petter; Gao, Zhen
Abstract: For installing offshore wind turbines into deep waters, use of floating crane vessels is essential. One of the major challenges is their sensitivity to wave-induced vessel and crane tip motions, which can cause the impact of lifted components like blades and nacelle with nearby structures. The impact loads on fibre composite wind turbine blades are critical as several complex damage modes, capable of affecting the structural integrity, are developed. Planning of such installation tasks therefore requires response-based operational limits that consider impact loads on the blade along with their damage quantification. The research area considering the impact behaviour of the lifted blade is novel, and thus, the paper identifies vessel, blade and lifting parameters that determine impact/contact scenarios. Furthermore, for a case in which a lifted blade with its leading edge impacts the tower, a numerical modelling technique is presented in Abaqus/Explicit, and a comprehensive damage assessment of the blade and an investigation of the impact dynamics and energy evolution are performed. Sensitivity studies for two distinct blade designs and two different impact locations are considered. The results show that 7–20% of the impact energy is absorbed as damage in the blade, whereas the majority dissipates as rigid-body motions of the blade after the impact. The findings of the study highlight the requirement for advanced installation equipment, such as active tugger lines, to prevent successive impacts of wind turbine blades during installation. Highlights: Floating crane vessels are sensitive to wave-induced vessel and crane tip motions and can cause impact of the lifted wind turbine blade with surrounding structures. The vessel, blade and lifting parameters which determine the impact scenarios are identified. A comprehensive impact investigation is performed in Abaqus/Explicit for a case in which the blade impacts the preassembled turbine tower with its leading edge. Sensitivity study for two distinct blade designs and two different impact locations are considered. The results show that 7-20% of the impact energy is absorbed as damage in the blade, whereas the majority dissipates as rigid-body motions.